Mechanistic insights on the alteration of nuclear waste glass from passivation to reactive diffusion in the environment - Pierre Frugier (npj Materials Degradation)
Abstract Vitrified wastes from nuclear fuel reprocessing are destined for permanent disposal in deep geological layers. Water will be the vector for glass alteration and the potential migration of radioactive elements. Modeling glass corrosion requires describing the amorphous layer on the glass surface and its effect on alteration kinetics. The GRAAL model (Glass Reactivity Allowing for the Alteration Layer) provides a simple equation to implement this passivation in reactive transport codes. The MOS model (MOdel Simplified) quantifies the contribution of the diffusive reactive environment to the alteration of vitrified nuclear waste in deep geological disposal. This involves the consumption of silicon by the repository near-field, affecting the alteration rate. Both models account for diffusion laws, leading to a glass alteration rate that decreases with time. This document formalizes the comparison of these two alteration models, allowing anticipation of conditions likely to cause one or the other mechanism to drive glass alteration.